Three-dimensional structure of a monomeric form of a retroviral protease - Veverka, Václav; Bauerová, Helena; Zábranský, Ales; Lang, Jan; Ruml, Tomás; Pichová, Iva; Hrabal, Richard (Journal of molecular biology, 2003)
The assembly of Mason-Pfizer monkey virus Gag polyproteins into immature capsids and their cleavage by the encoded protease are temporally and spatially separated processes, making the virus a particularly useful model for investigation of protease activation. Here we present a high resolution NMR structure of a fully folded monomer of a 12 kDa M-PMV protease (wt 12 PR) and of a Cys7Ala/Asp26Asn/Cys106Ala mutant (12 PR(D26N/C7A/C106A)). The overall structures of both wt 12 PR and 12 PR(D26N/C7A/C106A) follow the conservative structural motif of other retroviral proteases. The most prominent difference from the canonical fold of retroviral proteases is the absence of the interfacial beta-sheet, which leads to the loss of the principal force stabilizing the dimer of M-PMV PR. The monomer-dimer equilibrium can be shifted in favor of the dimer by adding a substrate or an inhibitor, partially compensating for the missing role of the beta-sheet. We also show that cysteines C7 and C106 play a crucial role in stabilizing the dimer and consequently increasing the proteolytic activity of M-PMV PR. This is consistent with the role of reversible oxidative modification of the cysteine residues in the regulation of the maturation of assembled M-PMV capsids in the cytoplasm.
Keywords: Masonův-Pfizerův opičí virus; Models, Molecular; Cysteine; Nuclear Magnetic Resonance, Biomolecular; nukleární magnetická rezonance biomolekulární; endopeptidasy; genové produkty gag; Endopeptidases; Mason-Pfizer monkey virus; Protein Denaturation; vazebná místa; zvířata; molekulární modely; Binding Sites; cystein; denaturace proteinů; Animals; terciární struktura proteinů; Protein Structure, Tertiary; Gene Products, gag